Study on the optimum value of remanent magnetism for suppressing ferromagnetic resonance of voltage transformer in all-cable line - Yonghao, Huang; Shuheng, Dan; Zhiyuan, Liu (Frontiers in Energy Research, 2024)
Introduction: Due to the need for safety and aesthetics, 10 kV urban power grids are gradually dominated by all-cable lines. However, this trend also brings new challenges. Cables, which are equivalent to capacitors at industrial frequency, are prone to resonate with the voltage transformers (PTs) in the system, causing drastic changes in current and voltage and posing a threat to the stable operation of the system. In addition, the intrusion of lightning waves into the substation will lead to different residual magnetization in the PT core, which further changes the core inductance value and affects the ferromagnetic resonance of the system to a certain extent. Methods: In order to deeply investigate the influence of remanent magnetism on the ferromagnetic resonance of the system, this paper establishes a simulation model of a 10 kV all-cable line based on the PSCAD software, and adopts a UMEC transformer capable of simulating the saturation characteristics to construct the PT, and simulates the intrusion currents by using a DC current source in order to generate remanent magnetism. By this method, the effect of remanent magnetization on the ferromagnetic resonance of the system is explored at different magnitudes and directions. Results: The results of the study show that the residual magnetization has a significant effect on the ferromagnetic resonant inrush current of the voltage transformer. When the remanent magnetization value is positive and less than 0.6 pu, the ferromagnetic resonance inrush current of PT can be effectively suppressed, and the smaller the remanent magnetization value is, the better the suppression effect is. However, negative remanent magnetization cannot suppress the ferromagnetic resonance of the PT, but may exacerbate the inrush current, leading to more serious consequences. Conclusion: This study helps to improve the stability of the power grid and also provides a valuable reference for future grid design and maintenance.